Association between serum 25‐hydroxyvitamin D concentrations and metabolic syndrome in the middle‐aged and elderly Chinese population in Dalian, northeast China: A cross‐sectional study. Issue 1 (21st June 2019) - Weldegiorgis, Tesfaye Zerfu; Hidru, Tesfaldet Habtemariam; Yang, Xiao‐lei; Xia, Yun‐long; Ma, Li; Li, Hui‐Hua
Abstract: Aims/Introduction: To investigate the association between serum 25‐hydroxyvitamin D (25‐[OH]D) concentrations and metabolic syndrome (MetS) in the middle‐aged and elderly Chinese population. Methods: The present study included 2, 764 participants (aged >50 years). The joint interim statement was used for the standard definition of MetS. Serum 25‐(OH)D concentrations were measured by electrochemiluminescence immunoassay. The study participants were categorized into quartiles based on serum 25‐(OH)D concentrations, and the quartiles were calculated for the differences using anova and the χ 2 ‐test for continuous and categorical data, respectively. A logistic regression analysis model was applied to estimate the odds ratios and 95% confidence intervals (95% CI) for each quartile of serum 25‐(OH)D concentrations compared with the highest quartile. Results: Serum 25‐(OH)D levels were markedly lower in men in the MetS group than in those without MetS. We observed a negative correlation between the higher quartiles of serum 25‐(OH)D levels and the presence of MetS among men. The correlation between serum 25‐(OH)D levels and the prevalence of MetS persisted even after adjusting for potential confounders, including age, cigarette smoking status, alcohol consumption, physical activity, low‐density lipoprotein, creatinine and total serum cholesterol. Adjusted odds ratios of MetS in the second through fourth compared with the lowest quartile for serum 25‐(OH)D levels were 0.93 (95% CI 0.54–1.59), 0.89 (95% CI 0.50–1.56) and 0.48 (95% CI 0.28–0.84), respectively. Conclusions: Decreased serum 25‐(OH)D level is significantly correlated with MetS in middle‐aged men. Abstract : Vitamin D and metabolic syndrome.